A Case Study of Ergonomics Prevention Program in a Machine Manufacture Industry - Wang, Pei-Chia; Yang, Cheng-Chun; Huang, Yen-Chun; Cheng, Yu-Sen (RSF Conference Series: Engineering and Technology, 2022)
Musculoskeletal Disorders (MSDs) is the most potential risks in human production and economic systems. In this research, ergonomics guidelines and enacted relevant regulations announced by other countries to effectively facilitate ergonomics prevention programs were discussed. A machine manufacture industry as a case study has been ergonomically evaluated by Musculoskeletal Disorders Checklist (MSDs) and Nordic Musculoskeletal Questionnaire (NMQ), which was used to recognize the dominating risk factors. According to the result of observation and preliminary assessment, low back pain related to the high frequency of manual material handling tasks was the critical issue in this case study. The conclusion revealed that the proposed improvement such as engineering redesign, training, health management, and administration, would be implemented into the main axle assembly area, customer service department, and Z-axis assembly area. The further improvement interventions would help organization to carry out the ergonomics prevention program.